Leap Motion Gesture Control With Carestream Software in the Operating Room to Control Imaging: Installation Guide and Discussion. (December 2015) - Pauchot, Julien; Di Tommaso, Laetitia; Lounis, Ahmed; Benassarou, Mourad; Mathieu, Pierre; Bernot, Dominique; Aubry, Sébastien
Nowadays, routine cross-sectional imaging viewing during a surgical procedure requires physical contact with an interface (mouse or touch-sensitive screen). Such contact risks exposure to aseptic conditions and causes loss of time. Devices such as the recently introduced Leap Motion (Leap Motion Society, San Francisco, CA), which enables interaction with the computer without any physical contact, are of wide interest in the field of surgery, but configuration and ergonomics are key challenges for the practitioner, imaging software, and surgical environment. This article aims to suggest an easy configuration of Leap Motion on a PC for optimized use with Carestream Vue PACS v11.3.4 (Carestream Health, Inc, Rochester, NY) using a plug-in (to download athttps://drive.google.com/open?id=0B_F4eBeBQc3yNENvTXlnY09qS00&authuser=0 ) and a video tutorial (https://www.youtube.com/watch?v=yVPTgxg-SIk ). Videos of surgical procedure and discussion about innovative gesture control technology and its various configurations are provided in this article.